Truncated-Unity Functional Renormalization Group for Multiband Systems With Spin-Orbit Coupling - Schober, Giulio A. H.; Ehrlich, Jannis; Reckling, Timo; Honerkamp, Carsten (Frontiers in Physics, 2018)
Although the functional renormalization group (fRG) is by now a well-established method for investigating correlated electron systems, it is still undergoing significant technical and conceptual improvements. In particular, the motivation to optimally exploit the parallelism of modern computing platforms has recently led to the development of the “truncated-unity” functional renormalization group (TU-fRG). Here, we review this fRG variant, and we provide its extension to multiband systems with spin-orbit coupling. Furthermore, we discuss some aspects of the implementation and outline opportunities and challenges ahead for predicting the ground-state ordering and emergent energy scales for a wide class of quantum materials.